Comparative outcomes of open retrorectus versus laparoscopic intraperitoneal onlay mesh repair of ventral hernia in a tertiary care center - Mukhamale, Vivek V.; Thakur, Bhushankumar A.; Deotale, Snehal; Mudgerikar, Rajas (International Surgery Journal, 2021)
Background: The combined Rives-Stoppa technique has been adopted as the gold standard for open incisional hernia repair. Laparoscopic intraperitoneal onlay mesh (IPOM) hernioplasty is a newer technique in managing ventral hernia. Based on this we have done single institution retrospective study of IPOM and open rectrorectus mesh repair for ventral hernia with size less than 5 cm. Methods: This study was single institution retrospective study, where we have analyzed the data of 30 patients in each group of ventral hernia, with median 18 months of follow up. Their data analyzed for demographics, surgical site occurrence and short terms recurrence. Results: Our study consists of 30 heterogenous population with similar age distribution in each group, mean time for surgery was 70.83 min for open and 66.33 minutes for IPOM. There was surgical site infection in 3 patients operated by open procedure and 2 patients in IPOM procedure. Duration of hospital stay which is more in open retrorectus repaired patients, 5.47 (mean) days and less in laparoscopic IPOM repaired patients, 5.07 (mean) days. Recurrence in both groups of patients is not seen in 6 months follow up in our study. Conclusions: Study supports safety in terms of duration of surgery, postoperative pain, surgical site infection, duration of hospital stays and efficacy in terms of return of normal activity and recurrence, equally effective in both open retrorectus and laparoscopic IPOM repair of ventral hernia with size less than 5 cm.